Metallosilicate catalyst solvent washing

JP7645245B2Active Publication Date: 2025-03-13DOW GLOBAL TECHNOLOGIES LLC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022515130
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-30
Filing Date
2020-09-29
Publication Date
2025-03-13
Estimated Expiration
2040-09-29

Smart Images

  • Figure 0007645245000001
    Figure 0007645245000001
  • Figure 0007645245000002
    Figure 0007645245000002
  • Figure 0007645245000003
    Figure 0007645245000003
Patent Text Reader

Abstract

The method includes the steps of (a) contacting a solvent having a water solubility of 1 g or more per 100 g of water with a metallosilicate catalyst having an alumina to silica ratio of 5 to 1500; and (b) heating the metallosilicate catalyst to a temperature of 125°C to 300°C for a period of 0.5 hours to 5 hours.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Technical Field FIELD OF THE DISCLOSURE This disclosure relates generally to metallosilicate catalysts, and more specifically to regenerating metallosilicate catalysts utilizing a solvent wash.

[0002] Introduction The production of secondary alcohol ethoxylate surfactants can be carried out by catalytic ethoxylation of (poly)alkylene glycol monoalkyl ethers ("monoalkyl ethers"). The monoalkyl ethers are formed from olefins and (poly)alkylene glycols using a metallosilicate catalyst. The metallosilicate catalyst provides selectivity to greater than 80% monoalkyl ethers, which is advantageous since (poly)alkylene glycol dialkyl ethers ("dialkyl ethers") are detrimental to the properties of secondary alcohol ethoxylate surfactants.

[0003] Although offering over 80% selectivity to mono-alkyl ethers, metallosilicate catalysts foul quickly, resulting in short service times, low mono-alkyl ether yields, and the need for repeated catalyst regeneration steps. Attempts have been made to wash the catalyst during the catalyst regeneration process. Regeneration of certain metallosilicate catalysts, for example by washing the catalyst in ethanol followed by drying at 150° C., has been found to be ineffective in restoring catalytic activity.

[0004] It is therefore surprising to discover a solvent wash regeneration process that regenerates metallosilicate catalyst monoalkyl ether production rates and selectivities comparable to unused metallosilicate catalyst. Summary of the Invention

[0005] The present invention provides a solution for providing a solvent wash regeneration process that regenerates metallosilicate catalyst monoalkyl ether production rates and selectivity commensurate with unused metallosilicate catalyst.

[0006] The present invention is the result of the discovery that washing a metallosilicate catalyst having a silica to alumina ratio of 5 to 1500 in a solvent having a water solubility of 1 gram (g) or more per 100 g of water during a regeneration process, followed by heating the catalyst to a temperature of 125° C. to 300° C. for a period of 0.5 to 5 hours, unexpectedly provides a catalyst with a monoalkyl ether production rate and selectivity comparable to that of a virgin catalyst. Such results are surprising in that prolonged heating of the washed catalyst to the boiling point of the wash solvent was found to be insufficient to restore catalytic activity; rather, the catalyst must be heated above the boiling point to restore catalytic activity. Moreover, the restoration of catalytic activity is surprising in light of the failure of the prior art to regenerate catalysts using similar solvent washing techniques.

[0007] According to at least one feature of the present disclosure, the method includes: (a) dissolving a solvent having a water solubility of 1 g or more per 100 g of water in a concentration of 5 to 1500; Silica to Alumina Ratio and (b) heating the metallosilicate catalyst to a temperature of from 125° C. to 300° C. for a period of from 0.5 hours to 5 hours. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] As used herein, the term "and / or," when used with a list of two or more items, means that any one of the listed items can be used by itself, or any combination of two or more of the listed items can be used. For example, if a composition is described as containing components A, B, and / or C, the composition can contain A alone, B alone, C alone, a combination of A and B, a combination of A and C, a combination of B and C, or a combination of A, B, and C.

[0009] Unless otherwise stated, all ranges are inclusive of the endpoints.

[0010] Test methods refer to the most current test method as of the priority date of this document unless the test method number is dated with a two-digit number with a hyphen. Test method references include both the testing society reference and the test method number. Test method organizations are referred to by one of the following abbreviations: ASTM refers to ASTM International (formerly known as the American Society for Testing and Materials), EN refers to European Norm, DIN refers to Deutsches Institut fur Normung, and ISO refers to the International Organization for Standardization.

[0011] The IUPAC codes describing crystal structures precisely as described by the Structure Committee of the International Zeolite Association refer to their most recent designations as of the priority date of this document, unless otherwise indicated.

[0012] As used herein, the term weight percent ("wt %") indicates that a component is a weight percent of the total weight of the indicated composition.

[0013] method The method of the present invention is directed to the regeneration of a metallosilicate catalyst. The method may include the steps of catalyzing a reaction of an olefin with an alcohol using a metallosilicate catalyst to produce an alkylene glycol monoalkyl ether, contacting the metallosilicate catalyst with a solvent having a water solubility of 1 g or more per 100 g of water, and heating the metallosilicate catalyst to a temperature of 125° C. to 300° C. for a period of 0.5 hours to 12 hours.

[0014] Olefins The olefins used in the present process can be linear, branched, acyclic, cyclic, or mixtures thereof. Olefins can be any combination of 5 carbons to 30 carbons (i.e., C5-C 30The olefin may have 5 or more carbons, or 6 or more carbons, or 7 or more carbons, or 8 or more carbons, or 9 or more carbons, or 10 or more carbons, or 11 or more carbons, or 12 or more carbons, or 13 or more carbons, or 14 or more carbons, or 15 or more carbons, or 16 or more carbons, or 17 or more carbons, or 18 or more carbons, or 19 or more carbons, or 20 or more carbons, or 21 or more carbons, or 22 or more carbons, or 23 or more carbons, or 24 or more carbons, or 25 or more carbons, or 26 or more carbons, or 27 or more carbons, or 28 or more carbons, or 29 or more carbons, while At the same time, it may have 30 carbons or less, or 29 carbons or less, or 28 carbons or less, or 27 carbons or less, or 26 carbons or less, or 25 carbons or less, or 24 carbons or less, or 23 carbons or less, or 22 carbons or less, or 21 carbons or less, or 20 carbons or less, or 19 carbons or less, or 18 carbons or less, or 17 carbons or less, or 16 carbons or less, or 15 carbons or less, or 14 carbons or less, or 13 carbons or less, or 12 carbons or less, or 11 carbons or less, or 10 carbons or less, or 9 carbons or less, or 8 carbons or less, or 7 carbons or less, or 6 carbons or less.

[0015] The olefin may be an alpha (α) olefin, an internally disubstituted olefin, or a cyclic structure (e.g., C3-C 12The alpha olefins may include alkenes such as cycloalkene. The alpha olefins include an unsaturated bond at the alpha position of the olefin. Suitable alpha olefins may be selected from the group consisting of propylene, 1-butene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-icosene, 1-docosene, and combinations thereof. The internal disubstituted olefins include an unsaturated bond that is not at a terminal position on the olefin. The internal olefins may be selected from the group consisting of 2-butene, 2-pentene, 2-hexene, 3-hexene, 2-heptene, 3-heptene, 2-octene, 3-octene, 4-octene, 2-nonene, 3-nonene, 4-nonene, 2-decene, 3-decene, 4-decene, 5-decene, and combinations thereof. Other exemplary olefins may include butadiene and styrene.

[0016] Examples of suitable commercially available olefins include NEODENE™ 6-XHP, NEODENE™ 8, NEODENE™ 10, NEODENE™ 12, NEODENE™ 14, NEODENE™ 16, NEODENE™ 1214, NEODENE™ 1416, NEODENE™ 16148 manufactured by Shell, The Hague, Netherlands.

[0017] alcohol The alcohols utilized in the present methods may contain a single hydroxyl group, may contain two hydroxyl groups (i.e., glycols), or may contain three hydroxyl groups. The alcohols may contain 1 or more carbons, or 2 or more carbons, or 3 or more carbons, or 4 or more carbons, or 5 or more carbons, or 6 or more carbons, or 7 or more carbons, or 8 or more carbons, or 9 or more carbons, while at the same time containing 10 or less carbons, or 9 or less carbons, or 8 or less carbons, or 7 or less carbons, or 6 or less carbons, or 5 or less carbons, or 4 or less carbons, or 3 or less carbons, or 2 or less carbons. The alcohol may be selected from the group consisting of methanol, ethanol, monoethylene glycol, diethylene glycol, propylene glycol, triethylene glycol, polyethylene glycol, monopropylene glycol, dipropylene glycol, tripropylene glycol, polypropylene glycol, 1,3-propanediol, 1,2-butanediol, 2,3-butanediol, 1,4-butanediol, 1,6-hexanediol, 1,4-cyclohexanemethanediol, glycerol, and / or combinations thereof. According to various examples, the alcohol is a (poly)alkylene glycol, such as monoethylene glycol, diethylene glycol, propylene glycol, and triethylene glycol.

[0018] The molar ratio of alcohol to olefin in the process can be from 20:1 or less, or 15:1 or less, or 10:1 or less, or 9:1 or less, or 8:1 or less, or 7:1 or less, or 6:1 or less, or 5:1 or less, or 4:1 or less, or 3:1 or less, or 2:1 or less, or 0.2:1 or less, while simultaneously being 0.1:1 or more, or 1:1 or more, or 1:2 or more, or 1:3 or more, or 1:4 or more, or 1:5 or more, or 1:6 or more, or 1:7 or more, or 1:8 or more, or 1:9 or more, or 1:10 or more, or 1:15 or more, or 1:20 or more.

[0019] Metallosilicate Catalyst As used herein, the term "metallosilicate catalyst" refers to an aluminosilicate (commonly referred to as a zeolite) compound having a crystal lattice in which one or more metal elements are substituted in place of silicon atoms. The crystal lattice of the metallosilicate catalyst forms internal cavities and channels in which cations, water, and / or small molecules may reside. The substitute metal elements may include one or more metals selected from the group consisting of B, Al, Ga, In, Ge, Sn, P, As, Sb, Sc, Y, La, Ti, Zr, V, Cr, Mn, Pb, Pd, Pt, Au, Fe, Co, Ni, Cu, Zn. The metallosilicate catalyst may be substantially free of Hf. According to various examples, the metallosilicate may have a silica to alumina ratio of 5:1 to 1,500:1 as measured using neutron activation analysis. The silica to alumina ratio can be from 5:1 to 1,500:1, or from 10:1 to 500:1, or from 10:1 to 400:1, or from 10:1 to 300:1, or from 10:1 to 200:1. Such silica to alumina ratios can be advantageous in providing a highly homogeneous metallosilicate catalyst with organophilic-hydrophobic selectivity for adsorbing non-polar organic molecules.

[0020] The metallosilicate catalyst may have one or more exchangeable cations on the exterior of the crystal lattice. The exchangeable cations are H + , Li + , Na + , Rb + , Cs + , Mg 2+ , Ca 2+ , Sr 2+ , B.A. 2+ , Sc 3+ , Y 3+ , La 3+ , R4N + , R4P + (R is H or alkyl).

[0021] Metallosilicate catalysts can have a variety of crystal structures. Specific examples of metallosilicate catalyst structures include MFI (e.g., ZSM-5), MEL (e.g., ZSM-11), BEA (e.g., β-type zeolite), FAU (e.g., Y-type zeolite), MOR (e.g., mordenite), MTW (e.g., ZSM-12), and LTL (e.g., Linde L), as described using the IUPAC code according to the International Zeolite Association Structure Commission nomenclature.

[0022] The crystalline framework of metallosilicate catalysts is represented by a network of molecular-sized channels and cages composed of corner-sharing tetrahedral [TO4] (T=Si or Al) primary building blocks. Negative charges can be introduced onto the framework via isomorphous replacement of tetravalent silicon of the framework by trivalent metal (e.g., aluminum) atoms. Overall charge neutrality is then achieved by the introduction of cationic species that compensate for the resulting negative lattice charge. When such charge compensation is provided by protons, Brønsted acid sites are formed, making the resulting H-form of the zeolite a strong solid Brønsted acid.

[0023] The metallosilicate catalyst can be used in the present process in various forms. For example, the metallosilicate catalyst can be a powder (e.g., particles having a longest linear dimension of less than 100 micrometers), granular (e.g., particles having a longest linear dimension of 100 micrometers or more), or a shaped article of powder and / or granular metallosilicate catalyst.

[0024] Metallosilicate catalyst is 100m 2 / g or more, or 200m 2 / g or more, or 300m 2 / g or more, or 400m 2 / g or more, or 500m 2 / g or more, 600m 2 / g or more, or 700m 2 / g or more, or 800m 2 / g or more, or 900m2 / g or more, while at the same time, 1000m 2 / g or less, or 900m 2 / g or less, or 800m 2 / g or less, or 700m 2 / g or less, or 600m 2 / g or less, or 500m 2 / g or less, or 400m 2 / g or less, or 300m 2 / g or less, or 200m 2 The surface area may be measured in accordance with ASTM D4365-19.

[0025] The metallosilicate catalyst can be synthesized by hydrothermal synthesis. For example, the metallosilicate catalyst can be synthesized by heating a composition containing a silica source (e.g., silica sol, silica gel, and alkoxysilane), a metal source (e.g., metal sulfate, metal oxide, metal halide, etc.), and a quaternary ammonium salt such as tetraethylammonium salt or tetrapropylammonium salt to a temperature of about 100°C to about 175°C until a crystalline solid is formed. The resulting crystalline solid is then filtered, washed with water, dried, and then calcined at a temperature of 350°C to 600°C.

[0026] Examples of suitable commercially available metallosilicate catalysts include CP814E, CP814C, CP811C-300, CBV 712, CBV 720, CBV 760, CBV 2314, CBV 10A manufactured by ZEOLYST INTERNATIONAL™ of Conshohocken, PA.

[0027] Formation of monoalkyl ethers Catalyzing the chemical reaction of an olefin with an alcohol using a metallosilicate catalyst results in an alkylene glycol monoalkyl ether. The alkylene glycol monoalkyl ether can be a (poly)alkylene glycol monoalkyl ether. The chemical reaction of an olefin with an alcohol is catalyzed by the metallosilicate catalyst in a reactor to produce a monoalkyl ether. Various monoalkyl ethers can be produced for different applications by varying which olefin is utilized and / or by varying which alcohol is utilized. The monoalkyl ethers are utilized for many applications, such as, for example, solvents, surfactants, chemical intermediates, etc.

[0028] The reaction of the olefin with the alcohol can occur at 50°C to 300°C, or 100°C to 200°C. In a specific example, the reaction can be carried out at 150°C. The reaction of the olefin with the alcohol can be carried out in a batch reactor, a continuous stirred tank reactor, a continuous fixed bed reactor, or a fluidized bed reactor. In a chemical reaction operation, the Bronsted acid sites of the metallosilicate catalyst can catalyze the etherification of the olefin to the alcohol through an addition type reaction. The reaction of the olefin with the alcohol produces a monoalkyl ether.

[0029] The addition reaction of olefins to glycols can form not only monoalkyl ethers, but also dialkyl ethers. Metallosilicate catalysts can exhibit selectivity to produce alkylene monoalkyl ethers but not dialkyl ethers. The monoalkyl ether selectivity of the metallosilicate catalyst can be 70% or more, or 75% or more, or 80% or more, or 85% or more, or 90% or more, or 95% or more, or 99% or more, while at the same time being 100% or less, or 95% or less, or 90% or less, or 85% or less, or 80% or less, or 75% or less. The selectivity of the dialkyl ether can be 0% or more, or 2% or more, or 4% or more, or 6% or more, or 8% or more, or 10% or more, or 12% or more, or 14% or more, or 16% or more, or 18% or more, while at the same time being 20% ​​or less, or 18% or less, or 16% or less, or 14% or less, or 12% or less, or 10% or less, or 8% or less, or 6% or less, or 4% or less, or 2% or less.

[0030] The yield of monoalkyl ether is calculated by multiplying the amount of olefin conversion by the selectivity of monoalkyl ether. The yield of alkylene glycol monoalkyl ether can be 10% or more, or 15% or more, or 20% or more, or 25% or more, or 30% or more, or 35% or more, while at the same time being 40% or less, or 35% or less, or 30% or less, or 25% or less, or 20% or less, or 15% or less. The yield of monoalkyl ether is a measure of the catalyst activity and selectivity, and is a good measure of the production rate of the metallosilicate catalyst.

[0031] During the reaction of olefins with alcohols, the catalyst becomes fouled, which has the effect of deactivating the catalyst (i.e., losing >50% of its etherification activity) within a few hours.

[0032] Contact of metallosilicate catalyst with solvent The regeneration of the metallosilicate catalyst is carried out by contacting the metallosilicate catalyst with a solvent followed by heating the metallosilicate catalyst. Contacting the metallosilicate catalyst with the solvent may be referred to as a "solvent wash". The solvent has a solubility in water (i.e., "water solubility") of 1 g or more per 100 g of water. Water solubility is measured according to ASTM D1722-09 at 101,325 Pa (1 atmosphere). The solvent may have a solubility in 100 g of water of 1 g or more, or 2 g or more, or 5 g or more, or 10 g or more, or 15 g or more, or 20 g or more, or 25 g or more, while at the same time being 30 g or less, or 25 g or less, or 20 g or less, or 15 g or less, or 10 g or less, or 5 g or less, or 2 g or less. As defined herein, water is a solvent that has a water solubility of 1 g or more per 100 g of water. It will be further understood that a water-miscible solvent is defined as having a solubility in 100 g of water of 1 g or more. The solvent may be selected from the group consisting of water, methanol, ethanol, 1-propanol, 2-propanol, t-butanol, 1,2-dimethoxyethane, acetone, acetonitrile, diethyl ether, ethyl acetate, methyl ethyl ketone, methyl isobutyl ketone, nitromethane, tetrahydrofuran, and combinations thereof.

[0033] The solvent may be contacted with the metallosilicate catalyst in various ways. For example, the solvent may be sprayed onto the metallosilicate catalyst, and / or the metallosilicate catalyst may be partially or completely suspended or immersed in the solvent. The solvent may be passed over the metallosilicate catalyst while it is still in the reactor (e.g., in a continuous fixed-bed reactor or a fluidized-bed reactor). In the suspended and / or immersed contact between the solvent and the metallosilicate catalyst, agitation (e.g., vortexing and / or shaking) may be applied to the combined catalyst-solvent system.

[0034] The solvent may be contacted with the metallosilicate catalyst for 30 seconds or more, or 1 minute or more, or 10 minutes or more, or 20 minutes or more, or 30 minutes or more, or 1 hour or more, or 2 hours or more, or 3 hours or more, or 4 hours or more, or 5 hours or more, or 6 hours or more, or 7 hours or more, or 8 hours or more, or 9 hours or more, or 10 hours or more, or 11 hours or more, or 12 hours or more, or 13 hours or more, or 14 hours or more, while simultaneously 15 hours or less, or 14 hours or less, or 13 hours or less, or 12 hours or 11 hours or less, 10 hours or less, 9 hours or less, 8 hours or less, 7 hours or less, 6 hours or less, 5 hours or less, 4 hours or less, or 3 hours or less, or 2 hours or less, or 1 hour or less, or 30 minutes or less, or 20 minutes or less, or 10 minutes or less, or 1 minute or less. During contact of the solvent with the metallosilicate catalyst, one or both of the solvent and the metallosilicate catalyst may be at a temperature of 10°C or more, or 20°C or more, or 30°C or more, or 40°C or more, or 50°C or more, or 60°C or more, or 70°C or more, or 80°C or more, or 90°C or more, or 100°C or more, or 110°C or more, or 120°C or more, or 130°C or more, or 140°C or more, or 150°C or more, while simultaneously being at a temperature of 160°C or less, or 150°C or less, or 140°C or less, or 130°C or less, or 120°C or less, or 110°C or less, or 100°C or less, or 90°C or less, or 80°C or less, or 70°C or less, or 60°C or less, or 50°C or less, or 40°C or less, or 30°C or less, or 20°C or less.

[0035] The solvent and metallosilicate catalyst can be separated from each other in various ways. For example, the solvent can be evaporated from the metallosilicate catalyst and the metallosilicate catalyst can be separated by centrifugation and / or other separation techniques. The contacting and separation of the metallosilicate catalyst and the solvent can be repeated.

[0036] Heating of metallosilicate catalysts After contacting the solvent and the metallosilicate catalyst, a step of heating the metallosilicate catalyst to a temperature of 125°C to 300°C for 0.5 hours to 5 hours is carried out. Heating the metallosilicate catalyst can be carried out in a variety of ovens, furnaces, and enclosures. For example, heating can occur in enclosures such as rotary kilns, box furnaces, fluidized bed furnaces, roller hearth kilns, tubes equipped with heating elements and mesh belt furnaces. Heating the metallosilicate catalyst can be carried out in a reactor (e.g., a continuous fixed bed reactor or a fluidized bed reactor). Heating the metallosilicate catalyst can be carried out in the absence of liquid (i.e., the metallosilicate catalyst can be dried before and / or during heating). In yet another example, the solvent can be boiled off the metallosilicate catalyst by the step of heating the metallosilicate catalyst.

[0037] Heating of the metallosilicate catalyst may be carried out in atmospheric oxygen, under an atmosphere that is inert to the catalyst and fouling on the metallosilicate catalyst, or under vacuum. The vacuum may be about 100,000 Pa or less, 50,000 Pa or less, 10,000 Pa or less, or 5,000 Pa or less. The inert atmosphere may include nitrogen, argon, helium, CO2, other gases that are inert to fouling, and / or combinations thereof. The inert atmosphere may include 60 volume percent ("vol %) or more, or 70 volume % or more, or 80 volume % or more, or 90 volume % or more, while at the same time 100 volume % or less, or 90 volume % or less, or 80 volume % or less, or 70 volume % or less of inert components. Volume percent is measured at the regeneration temperature as the percent of volume occupied by inert components divided by the total cavity space in which the metallosilicate catalyst resides, at the regeneration temperature. Such an inert atmosphere may be achieved by passing an inert gas at a constant rate over the metallosilicate catalyst during heating.

[0038] Heating of the metallosilicate catalyst may be carried out at a temperature of 125°C or more, or 150°C or more, or 175°C or more, or 200°C or more, or 225°C or more, or 250°C or more, or 275°C or more, while simultaneously being 300°C or less, or 275°C or less, or 250°C or less, or 225°C or less, or 200°C or less, or 175°C or less, or 150°C or less.

[0039] Heating of the metallosilicate catalyst may be carried out for 30 seconds or more, or 1 minute or more, or 10 minutes or more, or 20 minutes or more, or 30 minutes or more, or 1 hour or more, or 2 hours or more, or 3 hours or more, or 4 hours or more, or 5 hours or more, or 6 hours or more, or 7 hours or more, or 8 hours or more, or 9 hours or more, or 10 hours or more, or 11 hours or more, or 12 hours or more, or 13 hours or more, or 14 hours or more, while simultaneously 15 hours or less, or 14 hours or less, or 13 hours or less, or 12 hours or 11 hours or less, 10 hours or less, 9 hours or less, 8 hours or less, 7 hours or less, 6 hours or less, 5 hours or less, 4 hours or less, or 3 hours or less, or 2 hours or less, or 1 hour or less, or 30 minutes or less, or 20 minutes or less, or 10 minutes or less, or 1 minute or less. EXAMPLES

[0040] material The catalyst was defined by the BEA structure, had a silica to alumina ratio of 25:1, and 680 m 2 / g and is commercially available as CP814E from ZEOLYST INTERNATIONAL™ of Conshohocken, PA.

[0041] 1-Dodecene is an alpha olefin available commercially as NEODENE™ 12 from the SHELL™ Group of The Hague, Netherlands.

[0042] Monoethylene glycol is liquid anhydrous ethylene glycol purchased from SIGMA ALDRICH™ having the CAS number 107-21-1.

[0043] DME is dimethoxyethane, a liquid anhydrous solvent purchased from SIGMA ALDRICH™ with CAS number 110-71-4.

[0044] Hexane is a liquid solvent purchased from FISHER CHEMICAL™ having the CAS number 110-54-3.

[0045] Methanol is a liquid anhydrous solvent purchased from SIGMA ALDRICH™ with CAS number 67-56-1.

[0046] Diglyme is bis(2-methoxyethyl) ether, a liquid anhydrous solvent purchased from SIGMA ALDRICH™ with CAS number 111-96-6.

[0047] Test Method Gas Chromatography Samples Prepare gas chromatography samples by mixing 100 μL of the sample with 10 mL of gas chromatography solution prepared by adding 1 mL of hexadecane in 1 L of ethyl acetate. Analyze the samples using an Agilent 7890B gas chromatography instrument. Analyze the total amount of 1-dodecene derived species, including mono-alkyl ethers, di-alkyl ethers, and 2-dodecanol, 1-dodecene and all non-1-dodecenes, other C 12 The total amount of dodecene, including isomers, is determined. Table 1 provides the relevant gas chromatography instrument parameters. [Table 1]

[0048] Time on Stream (TOS) The TOS of the catalyst is calculated by measuring the total time the catalyst is in contact with monoethylene glycol, 1-dodecene, catalyst and product at temperatures above 60°C.

[0049] Olefin Conversion Calculate the olefin conversion by dividing the total amount of dodecene-derived species by the sum of the total amount of dodecene-derived species and the amount of dodecene. Multiply the quotient by 100.

[0050] Monoalkyl ether selectivity Calculate the selectivity for mono-alkyl ethers (ME) by dividing the total amount of mono-alkyl ethers by the total amount of dodecene-derived species. Multiply the quotient by 100.

[0051] Monoalkyl ether yield The monoalkyl ether yield is calculated by multiplying the olefin conversion value by the monoalkyl ether selectivity value.

[0052] Catalytic activity The catalyst activity is calculated by dividing the grams of monoalkyl ether produced by the grams of catalyst used and dividing the quotient by the reaction time.

[0053] Sample preparation Unused catalyst A portion of virgin catalyst from the supplier is placed on a ceramic tray and calcined in a box oven with constant air flow at a temperature of 550° C. for 12 hours.

[0054] Spent catalyst A 300 milliliter (mL) Parr reactor with heating jacket and controller is charged with 67 g of monoethylene glycol, 62 g of 1-dodecene, and 7.5 g of powdered catalyst. The reactor is sealed and heated to 150° C. under agitation from a pitch blade impeller at 1100 revolutions per minute (rpm) for 3.5 hours. The reactor contents are removed and the catalyst is isolated via centrifugation using a SORVALL™ legend X1R centrifuge from THERMO SCIENTIFIC™. Repeat four times to generate sufficient spent catalyst. Transfer the spent catalyst to four ceramic dishes and dry the spent catalyst in a box oven with a constant air flow at 105° C. for 8 hours. Grind the dried spent catalyst into a powder using a mortar and pestle. Place the powdered catalyst in a bottle to create a single source of dry spent catalyst.

[0055] Catalyst Solvent Wash Load 1.5 g of dried spent catalyst with 40 ml of solvent into a 50 mL centrifuge tube at 23° C. Suspend the catalyst via vortexing for 1 minute using a K-550-G vortex mixer from VWR™. Shake the catalyst and solvent for 30 minutes using a Junior Orbit shaker from LAB-LINE INSTRUMENTS™ Inc. Isolate the catalyst via centrifugation while decanting off the supernatant solvent. Repeat two more times. Split the washed catalyst into two portions for testing. Heat one portion of the sample to the specified temperature for the specified number of hours (H).

[0056] Sample Testing Test the etherification activity using a 40 mL vial reactor and a rare earth magnetic stir bar set for tumbling agitation. Charge the reactor with 0.2 g of catalyst, 6.2 g of 1-dodecene, and 6.7 g of monoethylene glycol. Heat the reactor to 150 °C for 1 h.

[0057] result Table 2 provides sample test results for Comparative Examples 1-8 ("CE1-CE8") and Inventive Examples 1-3 ("IE1-IE3"). Table 2 provides data on olefin conversion, monoalkyl ether selectivity ("ME selectivity"), and monoalkyl ether yield ("ME yield"). CE1 is a fresh sample, while CE2 is a sample of spent catalyst. CE3-CE6 represent samples that have undergone a solvent wash but are only heated to 105°C, while IE1-IE3 utilize a solvent wash and are heated to 165°C. CE8 represents a sample that utilizes a solvent wash with a solvent that has a water solubility of less than 1g per 100g of water, but is heated to 165°C. Water as a solvent has a water solubility of greater than 1g per 100g of water. Methanol is miscible with water and therefore has a water solubility of greater than 1g per 100g of water. Dimethoxyethane is miscible with water and therefore has a water solubility of greater than 1g per 100g of water. Hexane has a water solubility of 0.0014 g per 100 g of water. [Table 2]

[0058] As is evident from CE3-CE6 in Table 2, solvent washing of the catalyst with a solvent having a water solubility of less than or greater than 1 g per 100 g of water and heating to 105°C only slightly increases the rate of mono-alkyl ether production compared to CE2 for the unwashed catalyst. IE1-IE3 demonstrate that washing the catalyst with a solvent having a water solubility of 1 g or more per 100 g of water followed by heating within the range of 125°C-300°C dramatically increases the olefin conversion (i.e., the rate of mono-alkyl ether production) with a level of mono-alkyl ether yield comparable to that of a virgin catalyst. CE8 demonstrates that hexane, having a water solubility of less than 1 g per 100 g of water, does not provide the same increased rate of mono-alkyl ether production even when heated to the same temperature. Considering the results, it is evident that only metallosilicate catalysts that are both washed with a solvent having a water solubility of 1 g or more per 100 g of water and heated within the range of 125°C-300°C exhibit mono-alkyl ether production rates and yields comparable to that of a virgin catalyst.

[0059] Fixed bed reaction test A fixed bed reactor for testing is created by loading 1.5 g of catalyst into a 40.64 cm long, 0.64 cm diameter 316 stainless steel tube reactor. The remaining space in the reactor is filled with 1 mm quartz chips. A piece of quartz wool is placed over each of the combined catalyst and quartz chips. The reactant feed lines are connected to the reactor and pumping power is provided at a flow rate of 0.1 ml / min to 0.2 ml / min using a Model 307 Gilson™ single piston pump. The reactor is heated to a temperature of 135°C in its reaction zone and the pressure in the reactor is maintained at 1 atm. The reactant feed consisting of 60 g of 1-dodecene, 60 g of monoethylene glycol, and 300 g of diglyme solvent is mixed into a single-phase mixture. The reactor is oriented so that the reactant feed flows down through the reactor. The reactant feed flows are started and the reactor is run for the specified time on stream.

[0060] Regenerate the catalyst in the reactor by first stopping the reactant feeds and then lowering the reactor temperature to 80°C. Purge the reactor with 50 mL / min N2 for 0.5 hours. Wash the catalyst with water at a feed rate of 1 mL / min for 150 minutes. Stop the water feed. Increase the reactor temperature to 180°C to dry the catalyst for 2 hours while purging the reactor with 50 standard cubic centimeters of N2 per minute. Lower the reactor temperature to 135°C, resume the reactant feeds, and resume the reaction.

[0061] Fixed bed reaction results Table 3 provides the results of the fixed bed reaction test. The catalyst regeneration step was carried out with a time on stream of 630 hours. [Table 3]

[0062] As is evident from Table 3, regeneration of the catalyst in a fixed bed reactor by first contacting the catalyst with water and then heating the catalyst to temperatures between 125° C. and 300° C. for periods of 0.5 to 5 hours significantly increased the catalyst activity (i.e., monoalkyl ether production rate) from 0.06 1 / hr to 0.33 1 / hr. Regenerating the catalyst without removing it from the fixed bed reactor is particularly advantageous in that the reactor does not need to be disassembled, the reactant feed can be exchanged for the solvent used for solvent washing, and the reactor can be used to dry the catalyst. (Aspect) (Aspect 1) 1. A method comprising: (A) contacting a solvent having a water solubility of 1 g or more per 100 g of water with a metallosilicate catalyst having an alumina to silica ratio of 5 to 1500; (b) heating the metallosilicate catalyst to a temperature between 125° C. and 300° C. for a period between 0.5 hours and 12 hours. (Aspect 2) 2. The method of embodiment 1, further comprising catalyzing a reaction of an olefin with an alcohol using the metallosilicate catalyst. (Aspect 3) The olefin is 12 ~C 14 The method of embodiment 2, comprising an olefin. (Aspect 4) The method of embodiment 2, wherein the alcohol is selected from the group consisting of monoethylene glycol, diethylene glycol, glycerol, and combinations thereof. (Aspect 5) The method of embodiment 2, further comprising the step of producing an alkylene glycol monoalkyl ether. (Aspect 6) The method of any one of aspects 1 to 5, wherein the step of heating the metallosilicate catalyst further comprises heating the metallosilicate catalyst to a temperature between 150° C. and 200° C. for a period between 0.5 hours and 5 hours. (Aspect 7) The method of any one of aspects 1 to 5, wherein the step of heating the metallosilicate catalyst further comprises heating the metallosilicate catalyst to a temperature between 125° C. and 300° C. for a period between 2 hours and 4 hours. (Aspect 8) The method of any one of aspects 1-7, wherein the solvent is selected from the group consisting of water, methanol, ethanol, 1-propanol, 2-propanol, t-butanol, 1,2-dimethoxyethane, acetone, acetonitrile, diethyl ether, ethyl acetate, methyl ethyl ketone, methyl isobutyl ketone, nitromethane, tetrahydrofuran, and combinations thereof.

Claims

1. 1. A method comprising: (A) contacting a solvent having a water solubility of 1 g or more per 100 g of water with a metallosilicate catalyst having a silica to alumina ratio of 5 to 1500; (b) heating the metallosilicate catalyst to a temperature of from 125° C. to 300° C. for a period of from 0.5 hours to 12 hours; using said metallosilicate catalyst to catalyze the reaction of an olefin with an alcohol.

2. The olefin is 12 ~C 14 The process of claim 1 comprising an olefin.

3. 2. The method of claim 1, wherein the alcohol is selected from the group consisting of monoethylene glycol, diethylene glycol, glycerol, and combinations thereof.

4. 10. The method of claim 1 further comprising the step of producing an alkylene glycol monoalkyl ether.

5. 5. The method of any one of claims 1 to 4, wherein the step of heating the metallosilicate catalyst further comprises heating the metallosilicate catalyst to a temperature of from 150°C to 200°C for a period of from 0.5 hours to 5 hours.

6. 5. The method of any one of claims 1 to 4, wherein the step of heating the metallosilicate catalyst further comprises heating the metallosilicate catalyst to a temperature of from 125°C to 300°C for a period of from 2 hours to 4 hours.

7. 7. The method of any one of claims 1 to 6, wherein the solvent is selected from the group consisting of water, methanol, ethanol, 1-propanol, 2-propanol, t-butanol, 1,2-dimethoxyethane, acetone, acetonitrile, diethyl ether, ethyl acetate, methyl ethyl ketone, methyl isobutyl ketone, nitromethane, tetrahydrofuran, and combinations thereof.

Citation Information

Patent Citations

  • Regeneration of thermally damaged zeolite catalyst

    JP1986038630A

  • Production of (Poly)Alkylene glycol monoalkyl ether and catalyst therefor

    JP1997052856A

  • Methods for regenerating and rejuvenating catalysts

    US20180318822A1

  • Hydrothermal activation of acid zeolites with alumina

    US4468475A

  • Dealumination and selective removal of organic material from zeolites

    US5425934A